The more the better - lower rate of stage migration and better survival in patients with retrieval of 20 or more regional lymph nodes in pancreatic cancer: a population-based propensity score matched and trend SEER analysis - Warschkow, René; Widmann, Bernhard; Marti, Lukas (Pancreas, 2017)
Objective The aim of this study was to assess the influence of regional lymph node (RLN) retrieval on stage migration and survival in pancreatic cancer. - Methods A total of 7685 stage I and II pancreatic cancer patients were identified in the Surveillance, Epidemiology, and End Results database in 2004-2011. The impact of RLN was assessed using Cox regression, propensity score methods, and joinpoint regression. - Results In 3079 patients, 1 to 10 RLNs were retrieved; in 2799 patients, 11 to 19 RLNs, and in 1807 patients, 20+ RLNs. The rate of node-positive pancreatic cancer increased with the number of retrieved RLN. This trend continued beyond 10 retrieved RLN (P < 0.001). In unadjusted analysis, retrieval of RLN did not influence survival (P = 0.178). When adjusting for significant bias in staging variables (P < 0.001), retrieval of 20+ RLNs compared to 11 to 19 RLNs was associated with an increased survival in node-negative (hazard ratio, 0.78; 95% confidence interval, 0.62-0.98; P = 0.033) and node-positive cancer (hazard ratio, 0.83; 95% confidence interval, 0.74-0.93; P = 0.002). - Conclusions This population-based propensity score-adjusted investigation demonstrated that more retrieved RLNs in pancreatic cancer decreases the rate of stage migration and improves the oncological outcome in node-negative and positive cancer. Contradictory results may be explained by a bias in the cancer characteristics for a different extent of RLN retrieval.